EVENTRATION OF DIAPHRAGM - Eka Pratiwi, I G A P; Purniti, P Siadi; Subanada, IB; Putu Yasa, Ketut (Medicina; Vol 39 No 1 (2008): Januari 2008, 2012)
Eventration of diaphragm (ED) refers to an abnormally high position of part or all of the diaphragm, but intact diaphragm, usually associated with a marked decrease in muscle fibers and a membranous appearance of the abnormal area with only the peripheral thoracic attachments showing normal muscle. Etiologically ED is congenital or acquired. Congenital diaphragmatic abnormalities occur in 1 per 2000 to 4000 birth, which 7% is diaphragmatic eventration. Most children with ED are asymptomatic when incidentally first seen, will not need theraphy. Those with symptoms develop acute respiratory distress, feeding difficulties, and recurrent pneumonitis. If the patient need assissted ventilation or cannot be weaned off the ventilator, she or he should be plicated. Failure to achieve extubation within a week of plication is an ominous prognostic sign. We reported a case of one month and four days old girl who was dispnea, feeding difficulty and bronchopneumonia caused by right ED with acquired etiology. Plication was done to repaired the symptom. But unfortunately this was not succeded because there was complication of postoperative treatment.
Keywords: eventration, child, plication